Corn Substitution with Sorghum to Increase Production Efficiency of Local Egg-Laying Duck Farmers in Polewali Regency - Agni Ayudha Mahanani; Sari Fatimah Mus (Jurnal Agripet, 2026)
This study aimed to evaluate the proximate composition and production performance of feed using sorghum as a substitute for corn. This study was conducted in two stages. The first stage, conducted at the Integrated Animal Husbandry Laboratory of the University of West Sulawesi, included feed preparation and a proximate analysis. The second stage included a feeding trial on laying ducks raised in an experimental pen in Polewali Regency, West Sulawesi, Indonesia. The treatments were formulated as follows: P0 = 100% corn and 0% sorghum; P1 = 25% corn and 75% sorghum; P2 = 50% corn and 50% sorghum; P3 = 75% corn and 25% sorghum; and P4 = 0% corn and 100% sorghum. This experiment used a completely randomized design (CRD) with five treatments and five replicates. The results of the first stage showed that sorghum increased crude protein and reduced crude fiber while maintaining comparable metabolizable energy levels. In the second stage, the best overall performance was achieved in P4, which showed the lowest feed consumption (125.52 gram/bird/day), best feed conversion ratio (3.54), highest production index (20.78%) and highest revenue above feed costs (Rp 11,050 cost/bird). These findings indicate that a diet containing 100% sorghum provides the best efficiency and production performance, indicating that sorghum can effectively replace corn as an energy source in laying duck diets.